Permeability change induced by dissociation of gas hydrate in sediments with different particle size distribution and initial brine saturation. (January 2021) - Sun, Jingjing; Zhang, Zhun; Wang, Daigang; Liu, Changling; Lu, Hailong; Song, Kaoping
Abstract: Permeability is critical to understand gas production behavior from hydrate reservoirs. The effects of particle size distribution and initial brine saturation on effective permeability of hydrate-bearing sediment during hydrate dissociation are poorly understood. In this study, X-ray CT imaging and Lattice Boltzmann simulations are combined to obtain a better understanding of sediment permeability changes during hydrate dissociation and the effects of particle size distribution and initial brine saturation. The results reveal that the dissociation of hydrate induced by depressurization starts from the part in contact with gas, causing a gradual increase in sediment effective permeability with decreasing hydrate saturation. When a critical hydrate saturation below 0.1 is reached, a sharper increase in permeability is found in sediments initially saturated with 50% brine than with 100% brine. To investigate the underlying relationship between hydrate morphology and sediment permeability, two topological parameters of an isolated hydrate cluster, equalivalent diameter and shape factor, are introduced. Phase topology analysis of hydrate clusters confirms that the partial water saturation method causes a more heterogeneous spatial distribution of hydrate at pore-scale. It also suggests that sediment with a narrower particle size distribution shows a faster increase in permeability and a more uniform hydrate morphology evolution with dissociation, no matter whether it is initially 50% or 100% brine saturated. A slower effective permeability increase and hydrate morphology evolution are achieved in initially 100% brine-saturated sediments, implying a more uniform dissociation of hydrate in pore space. Highlights: The effects of particle size and initial brine saturation on permeability change during hydrate dissociation are explored. Topology analysis confirms that the partial water saturation method causes heterogeneous distribution of methane hydrate. Sediment permeability slowly increases with hydrate dissociation, followed by a sharp rise as hydrate saturation is below 0.1. Sediment with a narrower particle size range shows a faster permeability rise and a slower morphology evolution of hydrate. A more uniform dissociation of methane hydrate in pore space of initially 100% brine-saturated sediments is observed.